ADVANCING AI-DRIVEN TISSUE ENGINEERING CONSTRUCTS THROUGH FUTURE DIRECTIONS IN REAL-TIME ADAPTATION, MULTI-MODAL INTEGRATION, AND PERSONALIZED SCAFFOLD DESIGN. - Shaik, Nazeer; Shaik, Ajman (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The integration of artificial intelligence (AI) in tissue engineering has emerged as a transformative approach to designing scaffolds that enhance tissue regeneration and integration. This paper presents the Adaptive Multi-Modal AI for Personalized Scaffold Design (AMAPS). This novel framework addresses the limitations of existing AI models in tissue engineering by incorporating real-time adaptation, multi-modal data integration, and personalized scaffold design. The AMAPS framework employs advanced algorithms to analyze diverse biological data, allowing for the dynamic adjustment of scaffold properties in response to the evolving needs of regenerating tissue. Through a comprehensive review of recent literature, we highlight the current state of AI-driven tissue engineering and the challenges faced by traditional models, including their inability to provide personalized solutions and their reliance on static datasets. By contrasting AMAPS with existing methodologies, we demonstrate significant improvements in prediction accuracy, scaffold integration rates, and patient satisfaction. Our findings suggest that AMAPS enhances scaffold performance and fosters a more patient-centric approach to regenerative medicine. This research paves the way for future developments in AI-driven tissue engineering, potentially revolutionizing scaffold design and improving clinical outcomes in regenerative therapies.